Effect of constant versus variable small‐group facilitators on students' basic science knowledge in an enquiry‐based dental curriculum. (12th July 2019) - Zahra, Daniel; Bennett, Jon; Belfield, Louise; Ali, Kamran; Mcilwaine, Clare; Bruce, Malcolm; Jones, Gill; Brookes, Zoe L.; Coelho, Catherine; Zaric, Svetislav
Abstract: Introduction: The role of small‐group facilitators is of pivotal importance for the success of curricula based on active learning. Disorganised tutorial processes and superficial study of the problem have been identified as main hindering factors for students' learning. The aim of this study was to evaluate the influence of consistency of facilitation on students' performance in knowledge‐based basic science assessments in a hybrid, enquiry‐based (EBL) undergraduate dental curriculum. Materials and methods: This was a retrospective study of 519 first‐ and second‐year undergraduate dental students, enrolled at Peninsula Dental School between 2013 and 2018. Twice in each academic year, students sat a 60‐item single‐best‐answer, multiple‐choice examination. Percentage and Z‐scores were compared between students whose EBL groups had the same facilitator throughout the academic year, and those whose EBL group was facilitated by different members of staff. All EBL facilitators were dentally qualified but with different levels of expertise in basic dental sciences, prior EBL facilitation, involvement in the curriculum design and university affiliation. Results: No statistically significant difference was observed in the percentage or Z‐scores of students whose EBL sessions were supported by consistent or variable facilitators in any of the 18 MCQ tests. Z‐scores of first‐year students were more variable than for second‐year students. In addition, pairwise comparisons revealed no statistically significant differences in students' Z‐scores between any of the permanent facilitators' groups. Conclusions: The results of our study may influence the design and delivery of enquiry‐based curricula as well as human resources management by shifting the focus from maintaining facilitator consistency to ensuring comparable training and approaches across facilitators.